The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1097/wnr.0000000000001842
|View full text |Cite
|
Sign up to set email alerts
|

Impact of transcranial alternating current stimulation on working memory and selective attention in athletes with attention deficit hyperactivity disorder: randomized controlled trial

Abstract: Objective The current study aimed to investigate the impact of transcranial alternating current stimulation (tACS) on working memory and selective attention in athletes with attention deficit hyperactivity disorder (ADHD). MethodsIn total 45 athletes with attention deficit hyperactivity disorder were randomly divided into three equal groups (sham, control and experimental groups). All participants in the sham and experimental groups received stimulations on the F3 and SO with a current of (10 HZ) 1 mA for 15 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…This protocol led to a significant P300 amplitude increase and omission-type errors improvement. The third study [ 48 ] used 10 stimulations of 10 Hz in ADHD athlete children and found a significant improvement in WM.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This protocol led to a significant P300 amplitude increase and omission-type errors improvement. The third study [ 48 ] used 10 stimulations of 10 Hz in ADHD athlete children and found a significant improvement in WM.…”
Section: Resultsmentioning
confidence: 99%
“…Randomized control trials (RCT) were assessed according to the Cochrane database RoB 2 tool [ 52 ], with the assessed domains being randomization process, deviations from intended interventions, missing outcome data, measurement of the outcome, selection of the reported result and overall bias. Out of 15 RCT, three were evaluated as “Some concerns” due to single-blind design [ 23 , 46 , 47 ], two due to insufficiently described statistical analysis [ 21 , 35 ], one due to unsuccessful blinding integrity [ 41 ], and one due to insufficiently described blinding procedure [ 48 ]. Eight studies were considered “Low risk” [ 22 , 28 , 29 , 34 , 40 , 42 , 49 , 50 ].…”
Section: Resultsmentioning
confidence: 99%